'Hierarchy' in the organization of brain networks. (13th April 2020) - Hilgetag, Claus C.; Goulas, Alexandros
Abstract : Concepts shape the interpretation of facts. One of the most popular concepts in systems neuroscience is that of 'hierarchy'. However, this concept has been interpreted in many different ways, which are not well aligned. This observation suggests that the concept is ill defined. Using the example of the organization of the primate visual cortical system, we explore several contexts in which 'hierarchy' is currently used in the description of brain networks. We distinguish at least four different uses, specifically, 'hierarchy' as a topological sequence of projections, as a gradient of features, as a progression of scales, or as a sorting of laminar projection patterns. We discuss the interpretation and functional implications of the different notions of 'hierarchy' in these contexts and suggest that more specific terms than 'hierarchy' should be used for a deeper understanding of the different dimensions of the organization of brain networks. This article is part of the theme issue 'Unifying the essential concepts of biological networks: biological insights and philosophical foundations'.